Tribological Phenomenon and Heat Generation in the Railway Wheel - Rail Contact - Beneš, Libor; Kaloč, Rudolf (Promet - Traffic&Transportation, 2014)
The paper provides a description of tribological aspects and the latest type of laboratory equipment which is expected to offer particular new knowledge in the field of railway wheel - rail contact phenomena diagnostics. The main considerations stated in this work imply that the coefficient of adhesion is among others dependent on contact temperature, and therefore it is possible to theoretically predict the value of the coefficient of adhesion. This fact has not been considered in the theory of adhesive contact so far. The entirely credible prognosis of the studied unfavourable effects is hardly satisfactorily solvable in theory. Hence, the authors present a new testing device by which the predicted effects will be verified. At the same time, the oscillation effect on the state of surface will be observed in the attached formulas. The work also implies that the effects evaluating possible initiations and local degradations of the contact area of railway wheel and rail are closely bound to the tribological effects that are comprehended here as dynamic processes. KEY WORDS: contact fatigue, railway wheel - rail contact, tribology, safety of transport